Maximum strength, rate of force development, jump height, and peak power alterations in weightlifters across five months of training - Hornsby, W. G.; Gentles, J. A.; MacDonald, C. J.; Mizuguchi, S.; Ramsey, M. W.; Stone, M. H. (Sports, 2017)
The purpose of this monitoring study was to investigate how alterations in training affect changes in force-related characteristics and weightlifting performance. Subjects: Seven competitive weightlifters participated in the study. Methods: The weightlifters performed a block style periodized plan across 20 weeks. Force plate data from the isometric mid-thigh pull and static jumps with 0 kg, 11 kg, and 20 kg were collected near the end of each training block (weeks 1, 6, 10, 13, 17, and 20). Weightlifting performance was measured at weeks 0, 7, 11, and 20. Results: Very strong correlations were noted between weightlifting performances and isometric rate of force development (RFD), isometric peak force (PF), peak power (PP), and jump height (JH). Men responded in a more predictable manner than the women. During periods of higher training volume, RFD was depressed to a greater extent than PF. JH at 20 kg responded in a manner reflecting the expected fatigue response more so than JH at 0 kg and 11 kg. Conclusions: PF appears to have been more resistant to volume alterations than RFD and JH at 20 kg. RFD and JH at 20 kg appear to be superior monitoring metrics due to their "sensitivity."